Analysis of The Influence of Learning Environment and Parental Support on Elementary School Students' Academic Achievement In Urban Areas - Vika Fransisca (PT Publikasiku Academic Solution, 2024)
In urban contexts, students often face challenges related to educational resources and parental involvement, which affect their academic achievement. This study aims to investigate the influence of learning environment and parental support on the academic achievement of primary school students in urban areas. Using a qualitative approach, data was collected through in-depth interviews and focus group discussions with students, parents and teachers. The findings showed that students who were in a supportive school environment and supported by active parents showed higher academic motivation and better resilience. The results highlight the importance of classroom resources, teacher engagement and consistent parental support as significant factors in student achievement. However, socioeconomic factors often limit parental involvement, suggesting the need for flexible school-based engagement programs. This research recommends that urban schools adopt collaborative strategies to improve in-school support and parental engagement, thus creating a comprehensive support network for students. The conclusion of this study suggests that strengthening school-parent partnerships and improving the classroom environment are critical to improving students' academic achievement.